Squamous cell carcinoma of the tongue: clinical and morphological analysis of 57 cases and correlation with prognosis - Marcelo Gadelha Vasconcelos; Rodrigo Porpino Mafra; Rodrigo Gadelha Vasconcelos; Ana Miryam Costa de Medeiros; Lélia Maria Guedes Queiroz (Sociedade Brasileira de Patologia Clínica, 2014)
Introduction: Oral squamous cell carcinoma (OSCC), which represents more than 90% of head and neck malignant neoplasms, has a poor prognosis due to its high frequency of lymph node metastasis and local invasion. Previous studies have investigated parameters related to the biological behavior of OSCC and its correlation with disease outcome (DO). Objective: To evaluate clinical and morphological data in cases of tongue squamous cell carcinoma (TSCC), correlating these findings with prognosis. Material and methods: Fifty-seven specimens of TSCC were obtained from patients undergoing surgical excision at a referral hospital in Natal, Brazil. Clinical data, such as tumor-node-metastasis (TNM) stage and DO, were collected from medical records. Hematoxylin and eosin-stained sections were analyzed regarding histological grade of malignancy (HGM), based on the system proposed by Bryne (1998) Results: The majority of patients (38.6%) were diagnosed as TNM stage III, and 57.9% developed metastases. Remission of the tumor occurred in 77.2% of the cases. The parameter "metastasis" exhibited a significant association with DO (p = 0) and TNM stage (p = 0.001), thus constituting a good indicator of tumor progression. Correlation of HGM and TNM stage with DO was not evidenced. Nevertheless, statistical analysis showed a significant association between HGM and TNM stage (p = 0.006). Conclusion: TNM clinical staging and HGM, evaluated in association, may be useful to estimate the prognosis of TSCC.